PENGARUH CITRA PERBANKAN DAN PELAYANAN TERHADAP KEPUASAN NASABAH BANK BNI CABANG KUALA TUNGKAL JAMBI - Fretty Welta; Gery Widagdo; Ratnasari (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2021)
The quality of the service system of a bank also deserves a consideration for customers because customers also seek convenience when making transactions. The quality of service at the Bank BNI Kuala Tungkal Jambi Branch, currently does not experience many problems, it's just that there are some customers / customers that I met felt they were still lacking in service. One of the factors that may influence customer decisions at Bank BNI Kuala Tungkal Jambi Branch is the less than optimal quality of service from the bank, such as the service that is not fast enough and the waiting room seats are not enough. Even though they are classified as middle to lower class society, they also want to be appreciated and served in a special way. This is important to consider because the middle to lower class is the market share of the Kuala Tungkal Jambi branch of BNI Bank. The service factor provided by the bank is one of the moderating research variables that strengthens or weakens the influence between the image of the bank and customer satisfaction.